MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA SMA MUHAMMADIYAH 1 BANJARMASIN PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN (Ksp) MELALUI MODEL PEMBELAJARAN PROBLEM SOLVING - Syarifah Syarifah; Sunarti Sunarti; Yudha Irhasyuarna (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2014)
Abstract. This study aims to (1) improve learning outcomes concept of solubility and solubility product, (2) determine the ability of students to learning affective solubility and solubility product, (3) determine students' response to the application of the learning problem solving in learning solubility and solubility product. This study uses classroom action research design, with 2 cycles. Each cycle consists of planning, action, observation and evaluation, as well as analysis and reflection. The subjects were students of class XI IPA SMA Muhammadiyah 1 Banjarmasin, amounting to 24 people. Data collection techniques using achievement test engineering and questionnaires. Data analyzed by percentage. The results showed that the solubility of the learning material and the solubility product of problem solving using learning model to improve learning outcomes of students from 76.83% in the first cycle to 84.26% in the second cycle with an increase of 7.43%. Affective abilities of students included in either category 76.5%. Students' response to the learning model of problem solving in learning solubility and solubility product showed a positive response of 85.8%.Keywords : problem solving, solubility and solubility product,learning out comes